Doubts in business communication – can we transform perception into message - Jovanovic, Dragana; Baltezarevic, Vesna; Baltezarevic, Radoslav (International Review, 2016)
The communication potential of virtual technology is widely recognized. Here, wereview current problems related to developing, evaluating, or using virtual technology inbusiness communication. Business uses of digital technology are broadly understood, butsome of the questions we discussed here raise confusion about virtuality and reality, mentalillusions, intransitive condition, and impassable boundaries of virtuality - embodied,sensual, singular subjectivity. Virtual communication is far beyond using computertechnology, as we know it today. However, we all should be aware of confusion related tocomputer-mediated perception. From individual perception, communication sometimemoves toward contemplative abstraction, which tends to forget its precondition: theoriginal, mediated perceptual-sensuous immediacy of physical existence in the world.Perception is the unmediated directness, original, non-objected participation of organismin the universe. That is existence in unity with things, coexistence with the world. Originalor phenomenological, sensory perception is not seen as a sign that the object emits andwhich informs us about it, or as structures of our brain centers or translation energy pulsesin the respective forms - all these ideas are subsequent, second level or secondary metalstructures. Perception is not noticed, but modus vivendi, manner of existence, the directparticipation in the universe. This is the metaphysical meaning of perception, which doesn`tdeny the necessity of action, forces us to treat perceptions as a message, but it is secondaryand derived meaning that we cannot legitimately absolutize.